The Constitutional Status of Regional Representative Institutions in Decentralized Systems: A Case Study of Indonesia’s Regional House of Representatives (DPRD) - Muhammad Aqim Al Mizan; Tomy Michael (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines the constitutionality of classifying members of Indonesia's Regional House of Representatives (DPRD) as regional officials under Articles 18 and 22E of the 1945 Constitution, analyzing its implications for representative democracy, institutional independence, and decentralized governance. Employing normative legal research, the study applies statutory, conceptual, and historical approaches to examine constitutional provisions, legislation, legal doctrines, judicial decisions, and scholarly literature, focusing on the evolution of the DPRD's institutional position under Laws No. 22/1999, 32/2004, and 23/2014. Findings demonstrate that subsequent legislative reforms have shifted the DPRD from a regional legislative body to an element of regional government administration, creating constitutional ambiguity regarding its institutional identity and weakening its representative status. This classification is inconsistent with constitutional principles, as DPRD members derive democratic legitimacy directly from general elections rather than executive authority. This study uniquely integrates constitutional analysis with the historical trajectory of DPRD positioning, an underexplored focus in Indonesian legal scholarship. Harmonization of the statutory framework is recommended by reaffirming the DPRD as a regional representative institution to promote legal certainty and democratic accountability. This research provides a constitutional critique and actionable recommendations for policymakers, contributing to the theoretical discourse on institutional positioning within Indonesia's decentralized governance system.